Cadê o horizonte ? : a ocupação urbana ao longo da Rio-Santos em São Sebastião, 1964-2000 - Sandoval, Cristina Cardoso (2014)
The present work aims to study the impact of the implementation of the Rio-Santos highway in São Sebastião - SP in terms of changes occurring in the occupation of the coastal districts, affecting and displacing local communities. As a research topic, we propose the study of the impacts of the urbanization triggered by the opening of the road Rio-Santos in the occupation of the coastal areas of São Paulo. To this end, we propose the approach chosen in three communities along the road, with different characteristics, which show larger or smaller impacts in terms of the displacement and the other consequences of it s farm estate, outlining a comparative analysis between the earlier, contemporary and later periods to road construction: the neighborhood of San Francisco and beaches of Toque-Toque Pequeno and Juquehy.